2018
DOI: 10.1016/j.tra.2017.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural effects of a tradable driving credit scheme: Results of an online stated adaptation experiment in the Netherlands

Abstract: A B S T R A C TThere is increasing interest in the application of tradable credit schemes in the context of personal travel. To anticipate the short-term effects of a distance-based tradable driving credit (TDC) scheme, an innovative stated adaptation experiment has been conducted. Using an activity-based approach, Dutch participants who frequently commute by car could reschedule their car-based activities and alter the travel pattern they reported in an online travel diary for a full week. This paper presents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 67 publications
2
13
1
Order By: Relevance
“…As expected, whether the scenario implies a loss or a gain does have an effect, as the surplus scenarios significantly differ from the 30% shortage scenario. Marginal price (credit price level) does not have an effect, which is similar to the findings of Dogterom et al (2018), using the same price levels.…”
Section: The Netherlandssupporting
confidence: 80%
See 4 more Smart Citations
“…As expected, whether the scenario implies a loss or a gain does have an effect, as the surplus scenarios significantly differ from the 30% shortage scenario. Marginal price (credit price level) does not have an effect, which is similar to the findings of Dogterom et al (2018), using the same price levels.…”
Section: The Netherlandssupporting
confidence: 80%
“…This income effect is also found in the wider road pricing literature (Kockelman & Kalmanje, 2005;Ubbels & Verhoef, 2005;Washbrook, Haider, & Jaccard, 2006;Rienstra et al, 1999). However, when Dogterom et al (2018), using three income levels, found an income effect, they only found middle income households to report a significantly higher willingness to change. The education effect is an effect that has not previously been reported in the very limited strand of literature on TDC behaviors.…”
Section: Synthesis Beijing -The Netherlandssupporting
confidence: 65%
See 3 more Smart Citations